2015
DOI: 10.1007/s40865-015-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Persistence: Female Offending from 14 to 25

Abstract: Purpose While violent crime among females has nearly doubled, research on crime still tends to focus on male offending. To better understand the developmental patterns of female crime, this study identifies the trajectories of female offending from ages 14-25 years and examines the risk factors for persistent offending. Female trajectories and risk factors for offending are compared to those from a matched sample of males. Methods Participants include 172 serious (largely felony level) offending females and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 65 publications
5
62
2
4
Order By: Relevance
“…Whereas men and women exhibit a similar unimodal pattern of offending and age of decline in offending, female involvement in crime is less frequent than that of their male counterparts , Cauffman et al 2015, D'Unger et al 2002, Fergusson & Horwood 2002, Moffitt 2001. Also, although women tend to have shorter criminal careers, the difference in duration may be driven by the later age of onset rather than an earlier age of termination.…”
Section: Trends Of Desistancementioning
confidence: 99%
“…Whereas men and women exhibit a similar unimodal pattern of offending and age of decline in offending, female involvement in crime is less frequent than that of their male counterparts , Cauffman et al 2015, D'Unger et al 2002, Fergusson & Horwood 2002, Moffitt 2001. Also, although women tend to have shorter criminal careers, the difference in duration may be driven by the later age of onset rather than an earlier age of termination.…”
Section: Trends Of Desistancementioning
confidence: 99%
“…Accumulating evidence suggests that childhood trauma exposure is likely a key risk factor for subsequent juvenile justice involvement (Kerig & Becker, 2010). Juvenile offenders are a particularly vulnerable population but those with histories of trauma exposure and/or symptoms of posttraumatic stress disorder (PTSD) have higher rates of recidivism, co-occurring disorders, school drop-out, and suicide attempts (Cauffman, Monahan, & Thomas, 2015; Haynie, Petts, Maimon, & Piquero, 2009; Wasserman & McReynolds, 2011; Wolff, Baglivio, & Piquero, 2015). Multiple investigators have argued persuasively that youth may cope with traumatic stress in ways that increase their risk of arrest, including using drugs to avoid distressing memories, running away from an abusive home, and carrying a weapon or joining a gang to prevent re-victimization (DeHart & Moran, 2015; Ford, Chapman, Mack, & Pearson, 2006; Kerig & Becker, 2010).…”
mentioning
confidence: 99%
“…Some researchers have made inroads into the phenomenon of women's desistance as well as shed some light on the risk factors that begin to explain persistent offending patterns among female samples [9,10,21,32,51,52,118]. For example, Cauffman et al [28] compared self-reported offending trajectories for nearly 200 serious female offenders to a matched sample of male offenders and found that among persisters represented in the dataset, women were more likely to have been exposed to violence, trauma, and unhealthy interpersonal relationships. Their analyses made use of data from the Pathways to Desistance study [85,107], which focused on juvenile delinquency and captured the experiences of men and women up to 25 years old.…”
Section: Review Of Empirical Literature On Age and Women's Desistancementioning
confidence: 99%
“…Not only are the processes that shape the age-crime curve necessarily gendered, but they are rather consistently timed where processes and their significance unfold at regularly anticipated intervals [28,76]. In other words, the timing of a given life course event suggests that an event's salience is linked to a given subject's age and that age effects matter a great deal [39].…”
Section: Introductionmentioning
confidence: 99%